Evaluation of Safety Awareness Among Workers Performance with Respect to Safety Hazard at Spiral Pipe Manufacturing Industry - Victor, Hilda; Yasak, Mohd Fuad (Progress in Engineering Application and Technology, 2023)
The title of the study is " Evaluation of Workers Performance Where Respect to Safety Hazard for Spiral Pipe Manufacturing Industry." The objective used is to identify safety awareness among manufacturing workers for Spiral Pipe Manufacturing, analyses safety awareness using statistical analysis by using Statistical Package for the Social Sciences (SPSS), and propose a mitigation plan for prevention and control measures to reduce the risk of safety hazards. Next, the method used to complete this project is through a questionnaire given to 102 respondents, which is through observation, a questionnaire, and a reference check. In this study, I have identified the level of safety awareness among manufacturing workers for spiral pipe manufacturing. The findings of the study show that workers are aware of the safety hazards they face every day at work, but through observation, some workers do not care about their safety and do work without proper procedures. In addition, safety hazard prevention control is also discussed in this study through "grand toolbox talks," "signage," and "training and drills." In conclusion, from this course work, I have learned about the performance of employees towards safety hazards through their awareness.